Parents' Perspective On Early Childhood Parenting - Atin Risnawati; Marhumah Marhumah; Naimah Naimah; Hamidah Hamidah (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
Guiding children to become intelligent people requires nurturing and educating children. The family is the environment most responsible for educating children. The purpose of this study was to determine the level of understanding of parents about early childhood parenting and to find out how the role of parents in caring for children aged 4-6 years in Berasan Mulya Village. This type of research is descriptive quantitative. The research subjects were 30 parents who had children aged 4-6 years in the village of Berasan Mulya. The data analysis technique was carried out by determining the score and processing the data, calculating the frequency of the data, then making a categorization in the form of a percent on the level of parental understanding of early childhood parenting. Collecting data using a questionnaire/questionnaire. The results of this study are that many parents in Berasan Mulya Village already understand the pattern of parenting to early childhood. The highest level of understanding of parenting based on parental education level is high school level with the highest percentage, while the highest level of understanding of parenting based on parenting profession is self-employed. The way parents care for children aged 4-6 years in Berasan Mulya Village according to the results of the questionnaire is that parents tend to use democratic parenting which explains that parents' understanding is included in the good category, because they prioritize the interests of children, but do not hesitate to guide them. Parents with this behavior are rational and always base their actions on ratios or thoughts.